Development of educational and communicative text-forming competence of schoolchildren through the use of elements of distance learning - Karol, Andrei D.; Tayanovskaya, Iryna V. (University Pedagogical Journal, 2026)
A comparison is made of data concerning the communication of participants in an experiment with the introduction of elements of distance learning and the preparation of statements in a traditional format. The differences in the quantitative values of the experimental indicators related to the use of conversational speech techniques (including phraseology) and metaphorical imagery demonstrate statistical significance, being higher in the case of using elements of the distance learning form. It is concluded that distance learning aimed at mastering the specifics of creating educational texts provides students with the opportunity to use and improve the skills of constructing reasoned evaluative statements and participating in a heuristic polylogue.